(untitled) (Research, Society and Development, 2023)
To describe the profile of health care-associated infections (HCAIs) of patients affected by COVID-19 admitted to the adult ICU of a Reference Hospital for Infectious Diseases from July 2020 to July 2021. This is a cross-sectional study, based on secondary data obtained from a Reference Hospital for Infectious Diseases and a Public Health Laboratory located in Goiás. In the period evaluated, there were 67 cases of HCAIs, of which ventilator-associated pneumonia was the most frequent topography, followed by laboratory confirmed primary bloodstream infections. Most HCAIs were associated with the use of invasive devices, with higher prevalence of mechanical ventilation. Regarding the microbiological profile, Klebsiella pneumoniae was the most isolated microorganism. The importance of continuous surveillance of procedures related to HCAIs and the monitoring of the microbiological profile of institutions as a tool for prevention and control of these infections are highlighted.